2003
DOI: 10.1161/01.hyp.0000081216.11623.c3
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Supine Hypertension and Orthostatic Hypotension in Autonomic Failure

Abstract: Abstract-Supine hypertension occurs commonly in primary chronic autonomic failure. This study explored whether supine hypertension in this setting is associated with orthostatic hypotension (OH), and if so, what mechanisms might underlie this association. Supine and upright blood pressures, hemodynamic responses to the Valsalva maneuver, baroreflex-cardiovagal gain, and plasma norepinephrine (NE) levels were measured in pure autonomic failure (PAF), multiple-system atrophy (MSA) with or without OH, and Parkins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
130
0
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(148 citation statements)
references
References 38 publications
8
130
0
10
Order By: Relevance
“…In terms of the natural history of supine hypertension in patients with MSA, our present data together with results from other studies suggest that supine hypertension may function as a predisposing factor for the development of hypertensive target-organ damage in the cerebrocardiac system. Interestingly, pressor agent use did not influence the incidence of supine hypertension in patients with MSA, which was in line with previous reports that supine hypertension occurred in patients with MSA regardless of pressor agent use [10]. Furthermore, in our study, the use of pressor agents and disease duration did not significantly correlate with the severity of WMH.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of the natural history of supine hypertension in patients with MSA, our present data together with results from other studies suggest that supine hypertension may function as a predisposing factor for the development of hypertensive target-organ damage in the cerebrocardiac system. Interestingly, pressor agent use did not influence the incidence of supine hypertension in patients with MSA, which was in line with previous reports that supine hypertension occurred in patients with MSA regardless of pressor agent use [10]. Furthermore, in our study, the use of pressor agents and disease duration did not significantly correlate with the severity of WMH.…”
Section: Discussionsupporting
confidence: 92%
“…The former is also a symptom of an impaired cardiovascular autonomic nervous system, and was thus not unexpected; although only 2 patients met the clinical criteria for OH (correlation was conducted with scale data). Previous studies have reported an association with OH and supine hypertension [44] which could serve as an explanation for non-dipping in PD. The association of non-dipping with UPDRS scores is also not surprising given that cardiovascular symptoms are scored as part of the UPDRS and that cardiovascular autonomic dysfunction generally tends to occur in the latter stages of PD.…”
Section: Discussionmentioning
confidence: 90%
“…multisystematrofi eller langtkommet Parkinsons sykdom). Nattlig hypertensjon er vanlig hos pasienter med nevrogen ortostatisk hypotensjon (10,11). Blodtrykket er normalt 10-20 % lavere om natten enn om dagen.…”
Section: Figur 2 a -H) Kontinuerlig Blodtrykksmåling Under Valsalvas unclassified
“…Forverring av ortostatiske symptomer etter måltider er vanlig hos pasienter med nevrogen ortostatisk hypotensjon (9). Det er også vanlig, men lite kjent, at pasientene har hypertensjon i liggende stilling (10,11). Det har vaert anbefalt å heve sengens hodeende for å motvirke dette (3).…”
unclassified